Nutritional status of infants with cow's milk allergy who consume breast milk vs. hypoallergenic formula - Mulya Safri; Aulia Rahman Putra; Vidya Chatmayani Mulya (Indonesian Pediatric Society, 2016)
Background Infants with CMA are prone to suffer malnutrition because of the inability to absorb nutrients due to bowel inflammation. Breast milk and hypoallergenic formula is the best nutritional intake in CMA infants.Objective To compare the nutritional status of CMA infants who were consumed breast milk and hypoallergenic milk.Methods We conducted a cross-sectional study included a total of 63 CMA infants aged 3-6 months collected by consecutive sampling. Infant’s nutritional status measured by anthropometric exam were divided into well-nourished (-2 to 2 SD) or malnourished (<-2 or >2 SD). Type of milk consumption were asked directly to parents/caregivers through interviews.Results Most of our subject are well-nourished (75%). The number of CMA infants who were consumed breast milk or hypoallergenik milk is not a lot of difference, 51% vs 49%, respectively. There is no significant difference between the nutritional status of CMA infants who consumed breast milk and hypoallergenic milk (P=0.61).Conclusion because there were no differences between the nutritional status of CMA infants who consumed breast milk and hypoallergenic milk. Therefore it is recommended giving breast milk or hypoallergenic milk for the first 6 months of life to reduce cow’s milk protein exposure.